The The Implementation of Digital Multimodal Composing for Speaking and 21st-Century Skills in Vocational High School - Rizka Fahma Sabila Haque; Francisca Maria Ivone; Nanang Zubaidi (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
English speaking skills and 21st-century competencies are crucial for vocational high school graduates, yet they remain low in Indonesia. Digital Multimodal Composing (DMC) strategies, especially when combined with a task-based approach, offer the potential to enhance both skills. Unfortunately, the implementation of DMC in this context remains rarely explored. This research aimed to explore the implementation of DMC on English-speaking and 21st-century skills in vocational high school. This is a qualitative case study, using observation and interview as data collection techniques. This study involved a class with 17 students majoring in Visual Communication Design and an English teacher. The finding revealed that the implementation of DMC followed the steps of Willis (1996) and had a great potential in developing speaking and 21st-century skills. However, the post-task stage was absent, which caused the learners to lose the opportunity to engage in linguistic review and language focus.